Imagination / Izza Syahida Abdul Karim - Abdul Karim, Izza Syahida (Faculty of Art and Design, 2021)
IMAGINATION artwork is a photo image of Batmobile made from toy building bricks, one of many toy building masterpieces created by Anas bin Sharel, aged 10 who has been diagnosed with Autism Spectrum Disorder (ASD) at the age of 5. It was inspired by Anas’s observation of Batmobile from a series of Batman films from 1989 until 2012 including the Award-winning 2017 The Batman Lego Movie. Batmobile is a fictional armored tactical assault car driven by superhero Batman to fight against crime. The Batmobile has appeared in every comic book, television, film, and video game and has since become part of popular culture. To date, Anas has built 5 versions of Batmobile including other Batman fictional vehicles such as Batjet, Batplane, Batwing & Batpod solely from his observations and memory of the films. Each and every person diagnosed with autism has a distinct set of strengths and challenges. As for Anas, learning and speaking have been a challenging journey. However, Anas is gifted with a wonderful imagination and creative thinking, by channelling his observation into a masterpiece.